Optical and Piezoelectric Properties of Mn-Doped ZnO Films Deposited by Sol-Gel and Hydrothermal Methods. (10th February 2019) - Vladut, Cristina Maria; Mihaiu, Susana; Tenea, Ecaterina; Preda, Silviu; Calderon-Moreno, Jose M.; Anastasescu, Mihai; Stroescu, Hermine; Atkinson, Irina; Gartner, Mariuca; Moldovan, Carmen; Zaharescu, Maria
Abstract : Nowadays, multifunctional materials are of high interest due to their ability to be used in different applications by controlling one or two parameters (e.g., morphology and/or dopant). Zinc oxide is an intensive-studied material because of its large usability. Recently, we have shown that the conduction, transparency, and charge carrier concentration of ZnO can be controlled by changing the dopants, leading to promising materials as transparent conductive oxide films. In this work, sol-gel (SG) and hydrothermal (HT) methods were used separately or in combination in order to obtain ZnO films doped with Mn (1, 2, and 5%) for possible application in transparent optoelectronics or as piezoelectric materials. The manganese (Mn) dopant in the form of anhydrous manganese acetate was used to obtain Mn-doped ZnO films. ZnO hydrothermal (HT) growth was made on a previously ZnO seed layer, formed by sol-gel method. The Mn-doped ZnO films were deposited on microscope glass and on Pt/Ti/SiO2 /Si substrates. A comparative characterization of the films for their structure, morphology, and optical and piezoelectric properties was achieved. SG films exhibit equiaxed nanoparticles, with diameters around 50 nm, while the films prepared by HT show a homogeneous morphology consisting of uniform 1D nanorods, sized about 30 nm diameter and 200–300 nm length. XRD diffractograms evidenced the presence of zincite phase (wurtzite structure hexagonally close packed), with an improvement in crystallinity of the HT films (compared with SG ones), which present a stronger tendency to be oriented along (002) plane (c-axis) at 2% at Mn. Spectroscopic ellipsometry shows that the films obtained by SG are much thinner than the ones obtained by HT and that the refractive index is increasing with the percent of dopant. The band gap energy was found to decrease with the Mn doping level from 3.28 eV (undoped ZnO) to 3.10 eV (ZnO doped with 5 at% Mn) for the samples deposited on Pt/Ti/SiO2 /Si. The maximum transmission is found for the undoped ZnO film and decreases with Mn concentration but remains over 78% in the visible range. From the piezoelectric tests, it was found that thed 33 coefficient is much larger for the HT samples in comparison with the SG samples, especially for 2 and 5 at% Mn. The optical and piezoelectric results could be of interest for applications in optoelectronic or piezoelectric devices.